El problema del abandono de los estudios universitarios. [The dropout problem in university study] - Lidia Cabrera; José Tomás Bethencourt; Pedro Alvarez Pérez; Míriam González Afonso (RELIEVE: Revista Electrónica de Investigación y Evaluación Educativa, 2006)
This article focuses on the dropout of university students, which in some cases can be as high as 50%. This study presents and analyses the dropout rates that are found in several Spanish universities. Using the results of national and international studies as background and the findings from our own investigation, we present a theoretical framework that identifies the definition of dropouts, the causes, the explanatory models and solutions used to understand this issue. The article concludes by presenting a critical perspective of university learning in relation to the social role that universities represent, and addresses the actual processes of change, particularly in light of the European convergence. En este artículo se analiza el fenómeno problemático del abandono de los estudios universitarios, que alcanza hasta el 50% en algunas titulaciones. Para ello, partimos de la presentación y análisis de los porcentajes de abandono de distintas universidades españolas. Posteriormente, al amparo de distintos estudios nacionales e internacionales, y nuestros resultados de investigación, elaboramos un perfil teórico que contempla: definición, causas, modelos explicativos y soluciones. Finalmente, ofrecemos una perspectiva crítica de la enseñanza universitaria, en relación al papel social que esta representa, y en relación a los actuales procesos de cambio, sobre todo el proceso de convergencia europea.